KATEGORI GABUNGAN TINDAK PIDANA PADA PERKARA PENAMBANGAN LIAR DALAM KAWASAN HUTAN PRODUKSI: The Combined Classification of Illegal Mining Crimes in Production Forest Areas The Category Of Cumulative Criminal Acts In Illegal Mining Cases In Production Forest Areas - Alicia Aline Rhegita; Vientje Ratna Multiwijaya (Faculty of Law, Universitas Trisakti, 2026)
Illegal mining in production forest areas is an illegal act that has a serious impact on environmental sustainability and forest governance. The problem becomes complex when a series of illegal mining acts meet the elements of more than one criminal provision, thus raising the issue of the cumulative category of criminal acts. The formulation of the problem in this study is how the form or category of cumulative criminal acts committed by the perpetrators in the case of illegal mining in the production forest area was decided in the Kendari District Court Decision Number 496/Pid.Sus/2022/PN. Kdi. The research method used is normative legal research with an analytical descriptive nature, using secondary data in the form of primary legal materials and secondary legal materials, which are analyzed qualitatively by drawing deductive conclusions. The results of the study show that the Defendant's actions meet the cumulatived category of criminal acts in the form of concursus realist that applies a penal system with a cumulative stelsel. The implementation of the penal system is very important to reflect the seriousness of the act and strengthen legal protection of production forest areas from illegal mining practices.